Effects on the Forward Bias Characteristics of Neutron Irradiated Si and GaAs Diodes - Che Omar, Nuurul Iffah; Alang Md Rashid, Nahrul Khair; Abdullah, J.; Abdul Karim, J.; Hasbullah, Nurul Fadzlin (Maxwell Science Publications, 2012)
The aim of this study is to investigate the effects on forward bias characteristics of neutron radiation on various commercially available silicon and GaAs diodes. The diodes were irradiated using the Pneumatic Transfer System (PTS) facility in Malaysian Nuclear Agency with neutron fluences up to 1012 neutron/cm2.s for an exposure time of 1, 3 and 5 min. The Forward Bias (FB) current-voltage (I-V) characteristics and doping profiles of the diodes were recorded before and after irradiation. It is observed that the FB leakage current of the silicon and GaAs diodes increases after irradiation. The increase in leakage current is interpreted as being due to an increase of generation-recombination traps created in the band gap after radiation. The doping concentration of GaAs diodes in FB is observed to decrease while the series resistance increases after irradiation which may be attributed to changes in doping concentration due to carrier removal by the defects produced.